2018
DOI: 10.7717/peerj.6108
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of contract-relax proprioceptive neuromuscular facilitation stretching of hip abductors and adductors on dynamic balance

Abstract: BackgroundBalance control has been shown to play a fundamental role both in everyday life and many athletic activities. An important component of balance control is the somatosensory information gained from muscle spindles and Golgi tendon organs. The changes in the muscle-tendon unit stiffness could alter the ability to detect and respond promptly to changes of an unstable environment. One of the procedures affecting muscle stiffness is stretching, and contract-relax PNF stretching (CRS) is considered as one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
5
0
3
Order By: Relevance
“…Furthermore, Handrakis et al (91) and Nelson et al (92) reported improved dynamic balance (single leg balance on a Balance System SD movable platform) and postural sway (time to maintain a stabilometer horizontal over two 30 s periods) after 10 min and 20 min of total SS, respectively. Alternatively, contract-relax PNF stretching has been reported to improve dynamic balance on a Biodex balance system and stabilometric platform (93,94) as well as impair dynamic balance on a stabilometric platform (95). With the literature demonstrating similar number of SS articles reporting either improved and impaired balance with SS, more research is necessary to ascertain whether SS is more likely to be beneficial or detrimental to balance and under which conditions it might have these different effects.…”
Section: Balancementioning
confidence: 99%
“…Furthermore, Handrakis et al (91) and Nelson et al (92) reported improved dynamic balance (single leg balance on a Balance System SD movable platform) and postural sway (time to maintain a stabilometer horizontal over two 30 s periods) after 10 min and 20 min of total SS, respectively. Alternatively, contract-relax PNF stretching has been reported to improve dynamic balance on a Biodex balance system and stabilometric platform (93,94) as well as impair dynamic balance on a stabilometric platform (95). With the literature demonstrating similar number of SS articles reporting either improved and impaired balance with SS, more research is necessary to ascertain whether SS is more likely to be beneficial or detrimental to balance and under which conditions it might have these different effects.…”
Section: Balancementioning
confidence: 99%
“…PNF contract relax antagonist stretching technique was better than PNF hold-relax stretching technique in improving the hamstring muscle flexibility (Ramachandran, 2018). A single dose of contract relaxes PNF stretching of hip abductors and adductors muscle improves mideolateral dynamic balance (Szafraniec, 2018).Repetitive highintensity stretching may cause heavy burden on muscle tissues, and pain caused by high-intensity stretching can hinder muscle performance. Moderate stretching intensity is recommended and considered conducive to maintaining the effects of stretching while ensuring its safety (Lim, 2018).…”
Section: Positive Effect Of Pnf On Physical Fitnessmentioning
confidence: 99%
“…PNF is a multifaceted exercise therapy method based on the theory of human development and neurophysiology, and it has important physiological and health benefits in improving trunk proprioception, muscle strength, exercise control, balance and endurance [20][21][22][23]. Recently, PNF training has been widely used by physical therapists to treat patients with chronic LBP, and the mechanism elicits a neuromuscular response by stimulating proprioceptors to relieve the symptoms of low back pain [24][25][26][27][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%